Understanding flooding events in Ghana: a social marketing and self-determination theory perspective - Tweneboah-Koduah, E.Y.; Adams, M.; Amoakoh, M.N.; Braimah, S.M. (Journal of Social Marketing, 2022)
Purpose: The purpose of this study is to deepen the understanding of individuals’ flood disaster mitigation behaviour through the theoretical lens of self-determination theory (SDT). Specifically, the paper examines the influence of autonomy, competence and relatedness on individuals’ self-determined motivation for flooding disaster mitigation. The study also examines whether self-determined motivation influences individuals’ flood disaster mitigation behaviour adoption. Design/methodology/approach – Through a cross-sectional survey design, the study used a quantitative research approach for data collection and analyses. Specifically, data was analysed using the structural equation modelling technique. Findings: The result of this study revealed that competence was the strongest predictor of self-determination motivation, followed by autonomy. The result further shows that self-determined motivation positively influences individual’s adoption of flood mitigation behaviour. However, the results showed that relatedness does not predict self-determined motivation for flood disaster mitigation. Practical implications: To enhance the effectiveness of flood disaster mitigation social marketing campaigns, the SDT psychological needs constructs (particularly competence and autonomy) can aid in assessing the motivation of the target population towards adopting mitigation behaviours. An assessment of motivation will help understand perception of flood risk and behavioural evaluation. The consideration of autonomy and competence on motivation will aid in developing effective campaigns to satisfy the needs of the target population. Originality/value: The paper adds to the limited research that used SDT to understand a social marketing phenomenon
Research Article
Keywords: Autonomy; Competence; Self-determined motivation